The Physical Characteristics of Atoms and Ions and Their Behavior During the Earth’s Creation - Kudryavtsev P. (Emerging Issues in Environment, Geography and Earth Science Vol. 3, 2023)
In this study, we looked for more support for this theory and demonstrated other outcomes that follow from it. The notion of the Earth’s heated beginning has been supported by a contemporary understanding of chemical element characteristics. The original hydride Earth hypothesis was the next stage in the development of this notion. It was investigated how the physical characteristics of atoms and ions affected their behavior during the Earth’s creation. The distribution of components in the protoplanetary disk may be calculated thanks to the correlation dependency that is discovered. It was established that the primary component of the protomaterial found in the region of Earth’s origin was hydrogen. In this instance, a number of chemical compounds developed, with hydrogen compounds—hydrides—representing the majority. The chemical compounds are forced to adopt stoichiometry and structure that would not be possible in air settings because of the 375 GPa pressure inside the Earth. It has been demonstrated that several chemical elements may produce simple hydrides and superhydrides, which are polyhydrides with a high hydrogen content, at high pressure in a hydrogen medium. Given the possibility of forming polyhydrides, there is the possibility of binding the initially available hydrogen in an amount that can reach 49.3 mole%. Young Earth could contain about 10.7 mass. % of hydrogen in hydrides, polyhydrides, and adsorbed form is almost twice higher than previous estimates. This fact additionally confirms the theory of the original hydride Earth. In hydrides, the occurrence of the phenomenon of superconductivity was discovered. Polyhydrides were shown as potential superconductors with a high critical temperature above 200 K. We, based on these data, hypothesized the presence of superconducting properties in the Earth’s core, which explains the presence of a magnetic field in the Earth, as well as the unevenness and instability of this field and the possibility of migration of the Earth’s poles. The fact that the Earth has a hydroid core causes its change in time due to the instability of hydrides. Several possible models for destroying the Earth’s core have been proposed. The calculations showed that models give close results. These results give predictions that can be measured. The proposed models also made it possible to estimate the initial size of the Earth. Possible ways of further testing the hypothesis of the initial hydride Earth is shown.